COMPARATIVE STUDY ON DECOLORIZATION EFFICIENCY OF BLUE AZO DYE-235 USING TIO2, V2O5 AND ZNO AS PHOTOCATALYSIS - Al-Anbari, Riyad; Hameed Al-Obaidy, Abdul; Abd, Eman (Journal of Engineering and Sustainable Development, 2016)
Decolorization of blue azo dye (Cibacron Blue FN-R) from simulated wastewater has been investigated as a function of the solar photocatalysis process. The photocatalysis activity using different catalysis was compared. Different parameters that affected the removal efficiency, including an initial concentration of dye, pH of the solution, catalysis dosage, and H2O2 concentration, were evaluated to find out the optimum operating conditions. The results proved that the optimal pH value for TiO2, V2O5, and ZnO were 2, 2, and 8, respectively and the best catalysis dosage was 500mg/L for TiO2, V2O5, and ZnO. In addition, the most efficient H2O2 concentration was 300,100, 100 mg/L for TiO2, V2O5, and ZnO respectively. The theoretical relationships described in the photocatalysis process have been predicted for the three catalyzes. It can be concluded, from these experiments, that the use of ZnO as a photocatalysis was found to be more efficient than TiO2 and V2O5 to remove blue azo dye from an aqueous solution.